International migration, remittances and the brain drain (The World Bank, 2006)
International migration, the movement of people across international boundaries, has enormous economic, social and cultural implications in both origin and destination countries. Using original research, this title examines the determinants of migration, the impact of remittances and migration on poverty, welfare, and investment decisions, and the consequences of brain drain, brain gain, and brain waste.